Pengaruh Electronic Word Of Mouth (eWOM) Terhadap Minat Beli Followers Instagram Pada Warunk Upnormal - Aditya Ayu Laksmi; Farah Oktafani (Jurnal Computech & Bisnis (e-Journal), 2017)
Along with the development of technology and information, Warunk Upnormal using social media Instagram as a place for promoting. From the results of the initial survey that researchers do indicate that the many comments that recommends Warunk Upnormal, causing people interested in being followers Instagram of Warunk Upnormal to get information and would like to visit Warunk Upnormal.This study aimed to analyze the effect of Electronic Word of Mouth towards purchase intention of  followers instagram Warunk Upnormal. The type of research used is descriptive and causal research with the method used is quantitative. The population in this study is Warunk Upnormal’s Instagram followers. The sampling technique that being used is nonprobability sampling with the sampling incidental sampling. This study was involving 400 respondents of followers Instagram Warunk Upnormal. This study uses simple regression analysis technique. Based on the results, it can be concluded that Electronic Word of Mouth has significant effect on purchase intention of followers instagram Warunk Upnormal. Based on the coefficient of determination (R2) calculation can  be known the magnitude of the effect of electronic word of mouth (X) variable on purchase intention (Y) was 14.9%. While the remaining 85.1% is influenced by other factors.  Keywords: consumer behaviour, electronic word of mouth, purchase intention.